Hybrid capacitor with improved ESR stabilization
Patent Information
- Application Number
- JP2024204016
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-08-20
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2041-08-18
AI Technical Summary
【0013】 本発明の特定の効果は、高温及び高電圧の付与時にハイブリッドカソードを利用する能力である。
Smart Images

Figure 2025026990000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Application No. 63 / 067,946, filed August 20, 2020, which is incorporated herein by reference.
[0002] The present invention relates to a hybrid capacitor with improved equivalent series resistance (ESR) stability at higher temperatures and voltages. More specifically, the present invention relates to an improved hybrid capacitor with a barrier layer on the cathode and a stabilizer to prevent decay of the conductive polymer. [Background technology]
[0003] The hybrid aluminum capacitor is a composite system with a dielectric-coated anode, a cathode, and a separator between the dielectric and the cathode. A conductive polymer between the dielectric and the cathode ensures the electrical connection between the anode and the cathode through the dielectric, creating the capacitive coupling. An electrolyte fills the separator / polymer structure as much as possible to promote self-healing in case of defects in the dielectric.
[0004] In this specification, there are three important interfaces in a hybrid capacitor: the interface between the dielectric and the polymer, the interface between the cathode and the polymer, and the interface between the electrolyte and the polymer. The interface between the dielectric and the polymer has little effect on the conductivity of the polymer. Direct contact between the polymer and the metal on the cathode surface, in combination with the interface between the electrolyte and the polymer, produces an electrochemical reaction that can convert the polymer to a non-conductive state. In fact, conductive polymer reduction can be observed during surge voltage overloading when a high leakage current is applied or when high cathodic polarization occurs. High cathodic polarization is a significant negative potential that results in sufficient direct current to electrochemically reduce a significant portion of the polymer.
[0005] The most common conductive polymers are conjugated polymers such as polyaniline (PANI), polyacetylene (PA), polypyrrole (PPy), polythiophene (PT), polyparaphenylene (PPP), and polyparaphenylenevinylene (PPV). Conjugated polymers exhibit higher conductivity in the positive bipolaron state, where the polymer is oxidized from the neutral state to the bipolaron state, as shown in Figure 1A for 3,4-polyethylenedioxythiophene (PEDOT), Figure 1B for PPy, and Figure 1C for PANI. The polaron state is formed by chemical or electrochemical oxidation of the neutral polymer chains, and further oxidation leads to the bipolaron state.
[0006] The bipolaron state corresponds to a high degree of p-doping, since the Fermi energy level approaches the highest occupied molecular orbital (HOMO). In some conducting polymers, neutral chains can be converted to polarons or bipolarons through protonation, such as by treatment with low pH solutions, but this must be considered as an intramolecular oxidation by protons. With PAN and PPY polymers, electrons must be accepted from the low-energy electronic level of the protons involved in the reaction, so the concentration must make the "hole" generation process from the accepted protons thermodynamically possible. In cases where protons are not involved, such as PEDOT, the polymer doping can only be made conductive through intermolecular oxidation.
[0007] Oxidation is a reversible process. Thus, to reduce the bipolarons back to the less conducting polaron state and the near non-conducting neutral state, the Fermi level must be raised or the electrochemical potential must be lowered for the polymer. Additionally, for reduction to occur, a source of electrons must be present and ion exchange must be allowed to maintain overall electrical neutrality. The reduction process can occur through chemical or electrochemical mechanisms.
[0008] Without an electrolyte, the reduction process would be severely inhibited due to the high activation barrier and the requirement for strong reducing agents, however, in hybrid capacitors containing electrolytes, the activation barrier is reduced by solvation of the reagents, adsorption, and ionic mass transfer.
[0009] Electrochemical reduction can also occur when the polymer is in direct electronic contact with a metal electrode, where the Fermi level is high enough to guarantee electron tunneling into the bipolaron or polaron band. When the bipolaron band is filled with electrons, the gap between the Fermi level and the Highest Unoccupied Molecular Orbital (HUMO), i.e., the valence band, becomes larger, resulting in a decrease in the overall polymer conductivity.
[0010] The present invention provides structural moieties that can mitigate the reduction of conductive polymers, thereby resulting in improved performance, particularly with respect to ESR at elevated temperatures and pressures. Summary of the Invention [Problem to be solved by the invention]
[0011] It is an object of the present invention to provide an improved hybrid capacitor that is stable at high temperatures and voltages. [Means for solving the problem]
[0012] A particular feature of the present invention is the presence of a barrier layer on the cathode that prevents electrochemical reduction of the conducting polymer, and a stabilizer that also provides protection against electrochemical reduction of the conducting polymer by competing with the conducting polymer for electrons. Effect of the Invention
[0013] A particular advantage of the present invention is the ability to utilize a hybrid cathode at high temperatures and high voltage applications.
[0014] As will be appreciated, these and other advantages are provided in a capacitor, more preferably a hybrid capacitor, that includes an anode with a dielectric thereon, a cathode with a barrier layer thereon, and a separator, conductive polymer, liquid electrolyte, and stabilizer disposed between the anode and cathode.
[0015] Yet another embodiment is provided in a method of forming a hybrid capacitor, the method comprising forming an anode with a dielectric thereon, forming a cathode with a barrier layer thereon, forming a separator, and forming an active element between the anode and cathode, the active element comprising a layered structure of a conductive polymer, a liquid electrolyte, a stabilizer, and the separator. [Brief description of the drawings]
[0016] [Figure 1A] FIG. 1A shows a schematic of the neutral to polaron and bipolar transitions for various conducting polymers. [Figure 1B] FIG. 1B shows a schematic of the neutral to polaron and bipolar transitions for various conducting polymers. [Figure 1C] FIG. 1C shows a schematic of the neutral to polaron and bipolar transitions for various conducting polymers. [Diagram 2] FIG. 2 is a graphical representation of a cyclic voltammogram for conducting a polymer film and a soluble stabilizer. [Diagram 3] FIG. 3 is a schematic representation of one embodiment of the present invention. [Figure 4] FIG. 4 is a schematic representation of one embodiment of the present invention. [Diagram 5] FIG. 5 is a schematic representation of one embodiment of the present invention. [Figure 6] FIG. 6 is a schematic representation of one embodiment of the present invention. [Figure 7] FIG. 7 is a schematic representation of one embodiment of the present invention. [Figure 8] FIG. 8 is a schematic representation of one embodiment of the present invention. [Figure 9] FIG. 9 is a schematic representation of one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present invention relates to an improved hybrid capacitor that mitigates electrochemical reduction of a conductive polymer. More specifically, the present invention relates to an improved hybrid capacitor in which stabilization of the conductive oligomer is provided by a combination of a barrier layer on the cathode and a stabilizing agent in the electrolyte or on the conductive polymer. The barrier layer mitigates electron transfer to the conductive polymer by minimizing the possibility of direct electronic contact between the metal of the cathode and the conductive polymer. The stabilizing agent mitigates electron transfer in solution or on the metal from reducing the conductive polymer by acting as an electron acceptor.
[0018] A barrier layer is preferably formed on the cathode surface prior to assembly of the capacitor working elements. The barrier layer reduces defects in the oxide coating of the cathode. A stabilizing agent is added to the electrolyte and / or polymer surface at the polymer / electrolyte interface.
[0019] To elucidate the degradation mechanism, we experimentally modeled the degradation mode based on the chemical equilibrium of PEDOT between the neutral and bipolaron states, as shown diagrammatically in Figure 1A. When the hybrid aluminum capacitor was overstressed by passing a high leakage current for a long period of time, a significant increase in ESR was observed. The high leakage current caused the conductive polymer to be electrochemically reduced. During the test ESR increased from a pre-test resistance of 14 mΩ (14 mOhm) to a range of 130 mΩ-160 mΩ (130 mOhm-160 mOhm) measured after the test. Upon opening the capacitor, oxidation of the polymer by oxygen from the air returned the conductive polymer to the bipolaron state. After 12 h of storage in air, the ESR was reduced to almost the initial level of 16 mΩ (16 mOhm).
[0020] Based on efforts to elucidate the degradation mechanism, it was found that both electrochemical reduction and oxidation mechanisms require an ion pool that can compensate for the charge change that occurs with electron transfer from the cathode. The electrolyte in hybrid capacitors provides the ion pool. Thus, polymer degradation through electrochemical reduction is one potential source of capacitor degradation, specifically, ESR instability when leakage voltage is high or surge voltage is significant.
[0021] Without being limited by theory, it is hypothesized that the liquid stabilizer inhibits the reduction of bipolarons to polarons and neutral states by preferentially accepting high energy electrons from the cathode, essentially draining the energy of the electrons through a series of intermediates to the final product. The final product is characterized by a low reduction-oxidation related Fermi level or a high electrochemical potential of oxidation. In this case, the polymer can ensure electrical conductivity between the electrode and the final electron acceptor, the stabilizer, without significant changes in the energy band structure of the polymer. The stabilizer acts as an electron acceptor and is reduced instead of the polymer. The final product does not affect the state of the polymer, either by an irreversible process or by a series of reversible processes.
[0022] The stabilizer has a first electrochemical reduction potential higher than the second electrochemical reduction potential of the polymer under identical conditions. However, the potential of the electrochemical reduction of the product is close to the potential corresponding to the HOMO or highest occupied bipolaron band, as shown in FIG. 2, in which a graphical representation of the cyclic voltammograms of a conductive polymer film and a soluble stabilizer is provided. The electrochemical reduction of the stabilizer and the oxidation of the product are shown relative to the neutral state and the highest potential of the bipolaron. In this case, the final product is not able to reduce the polymer from the bipolaron state. Moreover, the final product may over-oxidize the polymer, since it requires gaining an electron from the valence band, which may lead to changes in the polymer structure / composition that affect the band diagram.
[0023] The present invention will now be described with reference to the drawings, which form an integral and non-limiting part of the specification and are provided for clarity of the invention, and in which like elements are numbered accordingly throughout the various figures.
[0024] An embodiment of the present invention is described with reference to FIG. 3, in which the working elements are shown in a schematic, partially exploded view prior to insertion into the container and, optionally, impregnation with, preferably, a liquid electrolyte. In FIG. 3, the working elements, generally designated as 10, include an anode 12 and a cathode 14 with a separator 16 disposed therebetween, which may be a conductive separator. The conductive separator may have a conductive polymer coated on it or the separator may be impregnated, preferably saturated, with a conductive polymer. An anode lead 20 and a cathode lead 22 extend from the wound capacitor and ultimately form electrical connections to the circuit. It will be understood from this description that the anode lead is in electrical contact with the anode and the cathode lead is in electrical contact with the cathode and electrically insulated from the anode or anode lead. Tabs 24 and 26 are generally employed to electrically connect the anode lead to the anode and the cathode lead to the cathode, as known in the art. A closure 28, such as an adhesive tape, prevents the active elements from unfolding during handling and assembly, after which the closure, while still a part of the finished capacitor, plays no significant role.
[0025] An embodiment of the present invention will now be described with reference to FIG. 4, in which a portion of a wound capacitor is shown in schematic cross-section. In FIG. 4, the anode 12 and cathode 14 have a dielectric 20 and a separator layer 22 disposed therebetween that form a capacitive coupling. Only one capacitive coupling is shown in the figure, with the understanding that the wound capacitor has an interleaved repeating combination of anode / dielectric / separator layer / dielectric. The separator layer, in one embodiment, comprises a separator with interwoven fibers 24. A conductive polymer 26, which may be formed prior to winding or introduced after winding, forms an electrically conductive path from the dielectric to the cathode. A stabilizer 18 is solidified on the surface of the conductive polymer. Optionally but preferably, a liquid electrolyte 28 at least partially, and preferably completely, fills the entire interstitial region of the separator. A barrier layer 32 is disposed over the cathode, preferably coating the cathode.
[0026] One embodiment of the present invention is described with reference to Figure 5, in which a portion of a wire wound capacitor is shown in schematic cross-section, where the anode 12 and cathode 14 have dielectric 20 and separator layer 22, with conductive polymer 30 and barrier layer 32 discussed with reference to Figure 4. The liquid electrolyte is a stabilized liquid electrolyte 28 that includes a liquid stabilizing agent dissolved in the liquid electrolyte.
[0027] The thickness of the barrier layer is preferably in the range of at least 1 nm to 500 nm or less. The main function of the barrier layer is to insulate the electrodes from the polymer while ensuring the required level of capacitance and efficient contact between the polymer layer, the barrier layer, and the metal for AC conductivity. The barrier layer may be porous.
[0028] The material of the barrier layer may be selected from any dielectric or insulator suitable for the application. Some metals suitable for use in capacitors, such as aluminum, are oxidized in air atmosphere to produce a thin oxide layer of about 1-2 nm, referred to in the prior art as native oxide. The thickness of the native oxide is insufficient to suppress direct electron transfer between the electrode metal and the conductive polymer. Therefore, when an oxide is used as the barrier layer, its thickness is preferably at least 3.0 nm to no more than 250 nm, with at least 40% of the surface area of the cathode being covered with the oxide. More preferably, at least 50%, more preferably at least 90%, and most preferably 100% of the surface is covered with the oxide. The dielectric constant of the barrier layer is preferably at least 2.0, more preferably at least 5.0, and most preferably at least 9.0, with barrier layers having higher dielectric constants being preferred.
[0029] Particularly suitable barrier layer materials include chemically or electrochemically formed alumina (Al 2 O 3 ), silica (SiO 2 ), silicates, H(OSiH 2 ) n OH and (OSiH 2 ) n where n is 1 to 5000, and the like, is a siloxane, an aluminum silicate [(Al 2 O 3 ) a (SiO 2 ) b (H 2 O) c ], phosphates, especially aluminum phosphate (AlPO 4 ), organic insulating polymers such as polyalkenes, especially (PP, PE), polyacrylates, polysaccharides, especially cellulose, chitosan or starch, and {(Ba 1-x Ca x )O} m {(Ti 1-y Zr y )O 2} 1-m , BaTiO 3 , Ba(Zr xTi 1-x )O 3 or Ba(Hf x Ti 1-x )O 3 where x is 0 to 1 and m is 0 to 1. The barrier layer may be amorphous or crystalline.
[0030] The main function of the stabilizer is to prevent changes in band energy levels in the polymer by draining electrons from the conducting polymer. The stabilizer can be either a solid stabilizer or a liquid stabilizer. Particularly suitable solid stabilizers are selected from insoluble organic peroxides, chelate complexes of transition metals on the polymer backbone. Soluble stabilizers include soluble peroxides, organic nitro compounds, and gas stabilizers.
[0031] The soluble organic peroxide is preferably a peroxide containing an alkyl group having 1-20 carbons or an aromatic group. The alkyl group can be linear or branched. The organic peroxide can be in solution, crosslinked or incorporated into an insoluble plasticizer, or preferably a gel matrix of insoluble organic peroxide. Exemplary organic peroxides are:
[0032] [ka]
[0033] And, Each R 1 , each R 2 , R 3 , and R 4 is independently selected from the group consisting of an alkyl group having 1-20 carbons or an aryl group, and n is 1-20.
[0034] The transition metal chelate complexes on the polymer backbone contain a metal cation and a number of blocks and ligands that are tailored to reach a reduction / oxidation potential higher than that of the polymer, as discussed above. Particularly preferred chelate complexes are
[0035] [ka]
[0036] wherein A is selected from the group consisting of Fe, Co, Os, and Ru; X is a unimolecular ligand preferably selected from the group consisting of heptafluorobutyrate, 4-nitrobenzoate, triflate, chloride, bromide, iodide, phosphate, phthalate, tosylate, hexafluorophosphate, tetrafluoroborate, and perchlorate; n is 1 or 2; m is 1-100; k is 1-100; and l is 1-100.
[0037] Organic nitro compounds have the chemical formula R 5 -R 6 -NO 2 wherein R 5 is selected from alkyl, alcohol, carboxyl, and hydroxyl groups up to 20 carbons; R 6 is aromatic C 6 Ring or substituted aromatic C 6 Suitable substituents on the ring include aromatic C 6 Substitution at the 2- or 3-position of the ring, aromatic C 6+4 Preferred are naphthalene, alkyl groups of up to 20 carbons, or hydroxyl groups, and most preferably R 6 is selected from the group consisting of (o,m,p)-nitroanisole, (o,m,p)-nitrobenzyl alcohol, (o,m,p)-nitrobenzoic acid, 4-nitrosalicylic acid, and 4-nitro-1-naphthoic acid.
[0038] A particularly suitable gas stabilizer is oxygen in a concentration range of 1 ppm to 1000 ppm of the total gas in the capacitor.
[0039] The hybrid capacitor configuration is not specifically limited herein, and the present invention may be embodied in any shape or form factor, including conventional designs such as V-Chip, Axial, SI, ST, Flat Pack, and others known in the art.
[0040] The method of forming the hybrid capacitor is not modified herein, except for the additional formation of the barrier layer on the cathode and the addition of the stabilizer. The hybrid capacitor can be fabricated by applying different methods for anode surface treatment, cathode barrier layer formation, and separator treatment / modification / fabrication.
[0041] The anode, cathode, and separator are typically prepared independently prior to assembly of the capacitor, including forming a dielectric on the anode and a barrier layer on the cathode. To form the conductive polymer in situ, it is preferred to form the conductive polymer layers on the anode and cathode by applying precursors such as monomers and oxidants, or by applying a polymer dispersion with or without selected additives. Polymer formation in hybrid capacitors is well known to those skilled in the art and includes forming the conductive polymer on the anode and cathode before the layer structure is formed, or after the wrapping layer is provided in the container.
[0042] The separator may be modified by applying a conductive polymer formed in situ from a monomer or by applying a preformed polymer dispersion, with or without selected additives, as is known in the art.
[0043] The electrolyte is usually provided with or without selected additives. The anode and cathode, with a separator between them, are wound to form a working element. After winding, the working element is optionally processed, including forming a dielectric or cathode barrier layer, post-polymerizing or applying a polymer dispersion to the working element through an in-situ process, drying, and washing. The working element is impregnated with the electrolyte after placing the working element in a housing or container, also called a can in the art. The housing is sealed, preferably hermetically sealed, under controlled conditions in which the gas atmosphere contains at least 50 ppm oxygen. The gas phase is preferably not more than 20% by weight of the can, more preferably not more than 10% by weight. The capacitor is usually aged after assembly tested at rated temperature and voltage prior to packaging.
[0044] The cathode foil, separator, and anode foil are typically provided as wide rolls and cut to size. The anode foil is preferably etched and a dielectric formed thereon. The dielectric may be formed prior to cutting, in which case the next step may be to form the dielectric at the slit edges. The separator is treated with a binder to improve adhesion between the surface and the conductive polymer layer or to impart other specific surface behavior. The conductive separator may be washed and dried before or after the conductive polymer layer formation or impregnation, and the conductive polymer layer formation or impregnation step may be repeated several times, if necessary. Electrical leads or tabs are typically electrically connected to the anode and cathode, preferably prior to cutting to length, and the leads may be treated with a masking material to protect them from further modification and to prepare them for welding to the capacitor terminations.
[0045] The conductive polymer is applied to the separator by any suitable method including impregnation, coating, or spraying. During impregnation, the separator is drawn through a series of baths or conduits with the monomer and oxidant being applied sequentially in any order. Impregnation is preferred for the separator. Coating and spraying may be applied by any printing technique including screen printing or spraying the monomer or oxidant sequentially, or in any order, or simultaneously onto the surface of the separator. The conductive polymer coating should have a concentration of at least 0.1 mg / cm. 2 It is preferred that the amount of the separator be about 0.1 mg / cm. 2 Below that, the coating weight is insufficient to provide sufficient conductivity, which can result in incomplete coating. Conductive polymer coatings are typically about 10 mg / cm 2 It is preferred that the coating be applied in an amount sufficient to achieve a coating weight of about 10 mg / cm. 2 Above this, the added coating thickness does not significantly increase the conductivity.
[0046] Multiple tabs or leads are preferred as they minimize the foil resistance effect. With a single lead, the current must flow from the furthest extension of the foil to the tab and lead, which is detrimental to ESR. Multiple anode and cathode leads are preferred to reduce the length of the conductive path.
[0047] The anode is a conductive metal, preferably in the form of a foil. The conductive metal is a valve metal or a conductive oxide of a valve metal. Particularly suitable anodes include tantalum, aluminum, niobium, titanium, zirconium, hafnium, alloys of these elements, conductive oxides thereof, such as NbO, etc. Aluminum is a particularly suitable anode material.
[0048] An oxide film is formed on the anode as a dielectric. The dielectric may be formed using any suitable electrolyte solution, referred to as a forming electrolyte, such as phosphoric acid or a phosphate-containing solution, boric acid or a borate-containing solution, or ammonium adipate. A forming voltage of about 9 V to about 450 V is typically applied. The forming voltage is typically in the range of 1.5 to 3.5 times the rated voltage of the capacitor.
[0049] The process for applying the conductive polymer is usually selected from in situ polymer formation and application of a preformed polymer from a slurry, such as by a coating process. In the in situ process, an impregnation solution is applied to the surface, where the impregnation solution preferably contains a monomer, an oxidant, a dopant, and other adjuvants known to those skilled in the art. Selection of a suitable solvent for the solution is well within the level of skill in the art. Examples of suitable solvents include ketones, alcohols such as acetone, pyridine, tetrahydrofuran, methanol, ethanol, 2-propanol, and 1-butanol. The monomer concentration may be about 1.5% to about 20% by weight, more preferably about 5% to about 15% by weight, in accordance with the present invention. Suitable monomers for preparing the conductive polymer include, but are not limited to, aniline, pyrrole, thiophene, and derivatives thereof. A suitable monomer is 3,4-ethylenedioxythiophene. The oxidant concentration may be about 6% to about 45% by weight, more preferably about 16% to about 42% by weight, in accordance with the present invention. Oxidizing agents for preparing conductive polymers include Fe(III) salts of organic and inorganic acids, alkali metal persulfates, ammonium persulfate, and others. A preferred oxidizing agent for demonstrating the present invention is Fe(III) tosylate. The dopant concentration may be about 5% to about 30% by weight, more preferably about 12% to about 25% by weight. Any suitable dopant may be used, such as polystyrene sulfonate, dodecylbenzene sulfonate, p-tosylate, chloride, and the like. A preferred dopant is p-tosylate. The substrate is cured at a temperature of 65°C to about 160°C, more preferably about 80°C to about 120°C, to polymerize the monomer. After curing, the polymer layer is preferably washed with deionized water or other solvent.
[0050] Applying a preformed polymer from a slurry after washing is a preferred method of introducing the conductive polymer into the winding. The polymer can be prepared or commercially available as a slurry without any particular restriction to the technique, and is preferably then dried. A slurry of polymerized 3,4-ethylenedioxythiophene doped with sulfonated polystyrene or other suitable dopant, with a particle size of 200 nm, preferably at least 1 nm to 200 nm, more preferably at least 20 nm to 200 nm, in a solvent, is exemplified for demonstration of the invention. Particularly preferred slurries have particle sizes indistinguishable by scattering techniques and are referred to as soluble conductive polymers.
[0051] The liquid electrolyte is preferably a solvent having a supporting salt therein. Any conventional solvent can be used, with example solvents including γ-butyrolactone, sulfonates, ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, acetonitrile, propionitrile, dimethylformamide, diethylformamide, water, silicone oil, polyethylene glycol, and mixtures thereof. A supporting salt is preferred, but not required. Example supporting salts include inorganic acid ammonium salts, inorganic acid amine salts, inorganic salt alkyl substituted amide salts, organic ammonium salts, organic acid amide salts, organic acid alkyl substituted amide salts, and derivatives thereof. Any gas absorbent or cathodic electrochemical depolarizer can be used. Example supporting additives include nitro derivatives of organic alcohols, acids, esters, aromatic derivatives such as o-, m-, p-nitroanisole, o-, m-, p-nitrobenzoic acid, o-, m-, p-nitrobenzene alcohol, and the like. Particularly preferred hybrid capacitors include up to 50% by weight of liquid electrolyte.
[0052] The separator is not particularly limited in this specification and any commercially available separator that can be used to demonstrate the present invention can be used, but it must be a material that can be used for a conductive separator that can be coated with or impregnated with a conductive polymer. As an alternative or in addition to a conductive polymer, the separator itself can be a conductive material. An example of a conductive separator is a separator that serves as a skeletal layer for the conductive polymer. The separator can be made in the form of a sheet of different dimensions that can be wound into a roll. The anode foil can serve as a support for the separator, in which case the anode foil has an insulator layer formed on its surface, a conductive polymer coating is provided on the insulator, and a conductive separator layer is formed on the polymer coating. The difficulty of operation can be minimized by using the anode as a support. The separator includes a porous conductive layer that creates a direct electrical contact between the anode conductive polymer layer and the cathode. Preferably, the separator has a quantity of pores that allows the passage of liquid electrolyte. Other non-conductive materials such as paper, polymer, etc. can be used as a support for the conductive polymer. Paper is an exemplary separator due to its widespread use and availability. Unlike conventional capacitors, paper does not need to be carbonized for use as a conductive separator. In conventional capacitor manufacturing, paper is often carbonized after the formation of the working element to minimize the amount of polymer absorbed by the paper. In accordance with the present invention, this is not necessary since the separator is coated or impregnated with a conductive polymer to form a conductive separator. The separator may be a fibrous material, such as paper fibers, physically intermingled or crosslinked to form continuous fibers, such as a paper fiber layer. The spaces between the fibers may be partially or completely filled with the conductive polymer. Paper-based separators can be produced by modification of the finished paper layer or paper prior to the formation of the paper layer with highly conductive component fibers and dispersion of conductive fibers, particles, particles, or agglomerates thereof in the liquid or solid state, or deposition of conductive fibers, particles, particles.The conductive fibers, flakes, particles may contain conductive materials such as conductive polymers, carbon black, graphite, metals, etc., or may be composite materials consisting of a non-conductive core of paper, plastic, etc. modified with a conductive material such as a conductive polymer, carbon black, graphite, metals, etc.
[0053] The conductive and non-conductive separators may comprise the same materials as the conductive separator with a conductive coating or impregnated with a conductor, although both are not required for the non-conductive separator.
[0054] Particularly suitable separators have a width suitable for the length of the active element or the manufacturing process, with 1.5 cm to 500 cm being examples for demonstrating the invention. The length is selected based on the desired capacity, since the capacity is a function of the overlap of the anode and cathode, which is directly related to the length and width of the cathode and anode. Separators with lengths of 0.1 m to 400 m and thicknesses of 10 μm to 300 μm are examples for demonstrating the invention.
[0055] The conductive polymer is preferably selected from polyaniline, polypyrrole, and polythiophene, or substituted derivatives thereof.
[0056] A particularly suitable conductive polymer is represented by Formula I: Chemical formula I
[0057] [ka]
[0058] In the formula, R 1 and R 2 is selected to prevent polymerization at the β-position of the ring. Most preferably, polymerization at the α-position only is allowed to proceed. Thus, R 1 and R 2 It is preferred that R is not hydrogen. More preferably, R 1 and R 2is an α-director. Therefore, ether bonds are preferred over alkyl bonds. To avoid steric hindrance, it is best for these groups to be small. For these reasons, both -O-(CH 2 ) 2 -O- and R 1 and R 2 In formula 1, X is S, N, or O, and most preferably X is S. A particularly suitable conductive polymer is polymerized 3,4-polyethylenedioxythiophene (PEDOT).
[0059] R 1 and R 2 independently represents a linear or branched C1-C16 alkyl or C2-C18 alkoxyalkyl, C1-C6 alkyl, C1-C6 alkoxy, halogen, or OR 3 or R is an unsubstituted or substituted C3-C8 cycloalkyl, phenyl, or benzyl. 1 and R 2 are both C1-C6 alkyl, C1-C6 alkoxy, halogen, C3-C8 cycloalkyl, phenyl, benzyl, C1-C4 alkylphenyl, C1-C4 alkoxyphenyl, halophenyl, C1-C4 alkylbenzyl, C1-C4 alkoxybenzyl, halobenzyl, or straight-chain C1-C6 alkylene unsubstituted or substituted with a 5-, 6-, or 7-membered heterocyclic structure containing two oxygen atoms. R3 preferably represents hydrogen, straight-chain or branched C1-C16 alkyl, or C2-C18 alkoxyalkyl, or C3-C8 cycloalkyl unsubstituted or substituted with C1-C6 alkyl, phenyl, or benzyl. In a particularly preferred embodiment, R 3 consists of an anionic group along with the corresponding cationic group, in which case Formula I is an intrinsically conductive polymer that does not require a counter ion, referred to as a self-doping polymer.
[0060] Various dopants can be incorporated into the polymer during the polymerization process as is commonly employed in the art. The dopants can be derived from various acids or salts, including aromatic sulfonic acids, aromatic polysulfonic acids, organic sulfonic acids with hydroxyl groups, organic sulfonic acids with carboxyl hydroxyl groups, alicyclic sulfonic acids, and benzoquinone sulfonic acids, benzene disulfonic acids, sulfosalicylic acids, sulfoisophthalic acids, camphor sulfonic acids, benzoquinone sulfonic acids, dodecyl benzene sulfonic acids, and toluene sulfonic acids. Other suitable dopants include sulfoquinones, anthracene monosulfonic acids, substituted naphthalene monosulfonic acids, substituted benzene sulfonic acids, or heterocyclic sulfonic acids, as exemplified in U.S. Pat. No. 6,381,121, which is incorporated herein by reference.
[0061] Optionally, binders and crosslinkers can also be incorporated into the conductive polymer layer. Suitable materials include poly(vinyl acetate), polycarbonate, poly(vinyl butyrate), polyacrylates, polymethacrylates, polystyrene, polyacrylonitrile, poly(vinyl chloride), polybutadiene, polyisoprene, polyethers, polyesters, silicones, and copolymers of pyrrole / acrylate, vinyl acetate / acrylate, and ethylene / vinyl acetate.
[0062] Other adjuvants, coatings, and related elements may be incorporated into the capacitor as known in the art without departing from the invention, including, by way of a non-limiting summary, protective layers, multiple capacitance levels, terminations, leads, and the like. EXAMPLES
[0063] Example 1: Hybrid capacitor samples were prepared based on carbon coated cathodes. Life tests showed that the samples showed a significant increase in ESR over time. Experiments were performed using 100uF (μF), 63V capacitors with 10mm diameter and 12.2mm length. Endurance tests were performed at 150°C and 63V. Three groups of capacitors were tested and the reported data was based on the average of five values. ESR at 100kHz was reported in mOhm (mΩ) as a function of time. The results are shown in Figure 6. In Figure 6, the control (no barrier) had no barrier on the cathode. The inventive sample had a barrier layer formed from a salt of phosphoric acid (phosphate) on the cathode. The other inventive sample had the same phosphate layer and additional oxide formed at 3Vf formation voltage to achieve 3-5nm additional aluminum oxide on the coated area of the aluminum cathode. All capacitors were similarly impregnated with 4-nitrobenzoic acid in the electrolyte. As shown in FIG. 6, the sample of the present invention exhibited excellent performance in terms of ESR darkening property.
[0064] Example 2: A series of hybrid aluminum capacitors were prepared for ESR testing. The average ESR curves as a function of time are shown diagrammatically in FIG. 7. In the top graph of FIG. 7, the carbon-coated cathode is compared to a cathode with an aluminum phosphate barrier layer. In the lower graph, the low leakage current is compared to the high leakage current for the cathode containing aluminum phosphate as a barrier layer. The curve for the carbon-coated cathode shows a slightly higher degradation at 135° C., with the ESR rising much faster. However, the leakage current is the same for both cathodes, indicating that the degradation is independent of voltage and occurs even at 0 V. Thus, the effect of the present invention is not voltage-dependent, and the present invention provides remarkable stability even at high voltages. The conductive polymer used in all examples was 3,4-polyethylenedioxythiophene with a commercially available sulfonated polystyrene dopant (PEDOT / PSS).
[0065] Physical analysis of the capacitors with increased ESR showed that the capacitor separator took on a violet color consistent with the reduced form of PEDOT / PSS. It can be concluded that the observed increase in ESR correlated with polymer reduction. Another important observation is that at 150 °C, a significant amount of gas was formed in the samples with carbon-coated cathodes and no barrier layer. Considering that the measured leakage currents were relatively low, the gas must have been formed through mechanisms that do not involve leakage currents, such as chemical or microcell electrochemical mechanisms. The aluminum phosphate protected cathodes showed reduced activity under cathodic polarization even after modification with the polymer (PEDOT / PSS). SEM and EDS spectra show that the barrier layer is mainly composed of aluminum phosphate, with a significantly higher concentration of phosphorus than in the etched layer. The cathode was protected by salt and direct electron transfer was suppressed on the surface, along with electrochemical and / or microelement electrochemical activity.
[0066] Example 3: A 63V 400uF (μF) hybrid capacitor was prepared, including an aluminum anode with a preformed dielectric layer with or without a nitro compound as a stabilizer, an aluminum cathode with a barrier layer formed from a salt of phosphoric acid, and an electrolyte including PEDOT / PSS as a conductive polymer, gamma butyrolactone (GBL), sulfolane, quaternary alkyl ammonium phthalate, and polyethylene glycol. The stabilizing effect of 4-nitroanisole (NA) is shown diagrammatically in FIG. 8, where the ratio between the ESR after 24 hours at 125°C / 63V and the initial ESR was recorded for several samples. The comparative sample (without NA) does not have 4-nitroanisole. In the sample of the present invention (NA), a relatively small ESR increase was observed after 24 hours of endurance testing, and for the sample without a stabilizer (without NA), a significant ESR increase was observed. The stabilizing effect of 4-nitrobenzoic acid (4NBA) is demonstrated in Figure 9, where the first part of the life test curves at 125°C / 63V for hybrid capacitor samples with and without 4-nitrobenzoic acid and with and without low leakage current are shown diagrammatically. Stable ESR curves were observed for the inventive samples, while a significant ESR increase was observed for the non-stabilized control sample (no 4NBA) after 120 hours.
[0067] While the present invention has been described with reference to preferred embodiments, without limitation thereto, those skilled in the art will recognize further embodiments which are illustrated and set forth in the appended claims.
Claims
1. A capacitor, an anode having a dielectric thereon; a cathode having a barrier layer thereon, the barrier layer being selected from the group consisting of silica, silicates, siloxanes, aluminum silicates, phosphates, organic insulating polymers, polyacrylates, polysaccharides, and ceramics; a separator between the anode and the cathode; a conductive polymer between the anode and the cathode; a liquid electrolyte between the anode and the cathode; a stabilizing agent in contact with the liquid electrolyte.
2. The barrier layer is 1-x Ca x ) O) m {(Ti 1-y Zr y }O 2 } 1-m (where m is 0 to 1), BaTiO 3 , Ba(Zr x Ti 1-x ) O 3 or Ba(Hf x Ti 1-x ) O 3 (where x is 0 to 1), polyalkenes, cellulose, chitosan, starch, H(OSiH 2 ) n OH, (OSiH 2 ) n 2. The capacitor of claim 1, wherein the anionic surfactant is selected from the group consisting of aluminum phosphate.
3. A capacitor, an anode having a dielectric thereon; a cathode having a barrier layer thereon, the barrier layer being an oxide; a separator between the anode and the cathode; a conductive polymer between the anode and the cathode; a liquid electrolyte between the anode and the cathode; a stabilizing agent between the anode and the cathode; the separator is present in the liquid electrolyte; the stabilizing agent is included in the liquid electrolyte between the anode and the cathode, the stabilizing agent being a transition metal chelate complex on a polymer backbone containing multiple blocks and ligands tuned to achieve a reduction / oxidation potential higher than that of the conductive polymer; The stabilizer is 【Chemistry 1】 And, A is selected from the group consisting of Fe, Co, Os, and Ru; X is a unimolecular ligand; n is 1 or 2; m is 1 to 100; k is 1 to 100; A capacitor, wherein l is selected from the group consisting of 1 to 100.
4. 4. The capacitor of claim 3, wherein X is selected from the group consisting of heptafluorobutyrate, 4-nitrobenzoate, triflate, chloride, bromide, iodide, phosphate, phthalate, tosylate, hexafluorophosphate, tetrafluoroborate, and perchlorate.
5. A capacitor, an anode having a dielectric thereon; a cathode having a barrier layer thereon, the barrier layer being an oxide; a separator between the anode and the cathode; a liquid electrolyte between the anode and the cathode; a conductive polymer between the anode and the cathode; a stabilizing agent at a polymer / electrolyte interface between the anode and the cathode; The stabilizer is an organic nitro compound, The organic nitro compound is R 5 -R 6 - NO 2 and R 5 is selected from alkyl, alcohol, carboxyl, and hydroxyl groups of up to 20 carbons; R 6 is aromatic C 6 Ring or substituted aromatic C 6 A capacitor is a ring.
6. The R 6 The capacitor of claim 5 , wherein is substituted with an alkyl or hydroxyl group of up to 20 carbons.
7. The R 6 is aromatic C 6 The capacitor of claim 6 , substituted at the 2- or 3-position of the ring.
8. The R 6 The capacitor according to claim 7, wherein is an aromatic naphthalene.
9. 6. The capacitor of claim 5, wherein the organic nitro compound is selected from the group consisting of 4-nitroanisole, 4-nitrobenzyl alcohol, 4-nitrobenzoic acid, 4-nitrosalicylic acid, and 4-nitro-1-naphthoic acid.
10. 1. A method of forming a hybrid capacitor, comprising: forming an anode having a dielectric thereon; forming a cathode having a barrier layer thereon; forming a separator; forming an active element between the anode and the cathode, the active element having a layer structure of a conductive polymer, a liquid electrolyte, a stabilizer, and the separator; the stabilizing agent comprises a chelate complex of a transition metal on the conductive polymer backbone; the transition metal chelate complex comprises a transition metal chelate complex on the conductive polymer backbone; The conductive polymer backbone comprises a metal cation and a number of blocks and ligands tuned to achieve a reduction / oxidation potential higher than that of the polymer; The stabilizer is 【Chemistry 2】 And, A is selected from the group consisting of Fe, Co, Os, and Ru; X is a unimolecular ligand; n is 1 or 2; m is 1 to 100; k is 1 to 100; The method wherein l is selected from the group consisting of 1 to 100.
11. 11. The method of forming a hybrid capacitor of claim 10, wherein X is selected from the group consisting of heptafluorobutyrate, 4-nitrobenzoate, triflate, chloride, bromide, iodide, phosphate, phthalate, tosylate, hexafluorophosphate, tetrafluoroborate, and perchlorate.
12. 1. A method of forming a hybrid capacitor, comprising: forming an anode having a dielectric thereon; forming a cathode having a barrier layer thereon; forming a separator; forming an active element between the anode and the cathode, the active element having a layer structure of a conductive polymer, a liquid electrolyte, a stabilizer, and the separator; The stabilizer comprises an organic nitro compound; The organic nitro compound is R 5 -R 6 - NO 2 and the stabilizing agent is at the polymer / electrolyte interface; R 5 is selected from alkyl, alcohol, carboxyl, and hydroxyl groups of up to 20 carbons; R 6 is aromatic C 6 Ring or substituted aromatic C 6 A method for forming a hybrid capacitor that is a ring.
13. The R 6 13. The method of forming a hybrid capacitor of claim 12, wherein is substituted with an alkyl of up to 20 carbons or a hydroxyl group.
14. The R 6 is aromatic C 6 14. The method of forming a hybrid capacitor of claim 13 , wherein the ring is substituted at the 2 or 3 position.
15. The R 6 The method of forming a hybrid capacitor of claim 13 , wherein is an aromatic naphthalene.
16. 13. The method of forming a hybrid capacitor of claim 12, wherein the organic nitro compound is selected from the group consisting of 4-nitroanisole, 4-nitrobenzyl alcohol, 4-nitrobenzoic acid, 4-nitrosalicylic acid, and 4-nitro-1-naphthoic acid.
17. 1. A method of forming a hybrid capacitor, comprising: forming an anode having a dielectric thereon; forming a cathode having a barrier layer thereon; forming a separator; forming an active element between the anode and the cathode, the active element having a layer structure of a conductive polymer, a liquid electrolyte, a stabilizer, and the separator; the stabilizing agent is in the liquid electrolyte; A method of forming a hybrid capacitor, wherein the stabilizing agent is oxygen.
18. 18. The method of forming a hybrid capacitor of claim 17, wherein said oxygen is at a concentration of 1 ppm to 1000 ppm of total gas in said capacitor.
Citation Information
Patent Citations
Manufacture of solid electrolyte capacitor
JP1990288216A
Electrolyte for electrolytic capacitor
JP1991068122A
Solid-state electrolytic capacitor and its manufacturing method
JP2001237146A
Solid electrolytic capacitor and its manufacturing method
JP2005109079A
Electrolytic capacitor
JP2008066502A